Application of Pharmaceutical Care Standards in the Drug Storage Phase at Pharmacy X Lingsar, West Lombok Regency, in Accordance with the Indonesian Ministry of Health Regulation Number 17 of 2024 - Hera, Alma (MEDFARM: Jurnal Farmasi dan Kesehatan, 2025)
Pharmacies, according to regulations, are vital locations within the healthcare service system. The aim of this research is to determine the implementation of pharmaceutical service standards at Pharmacy X Lingsar, West Lombok Regency, specifically during the drug storage phase. This study employs a descriptive observational method, involving direct observation of the storage system using a checklist at Pharmacy X Lingsar, located in Lingsar District, West Lombok Regency. The research findings indicate the following compliance rates: Spatial Arrangement 83.33%, Drug Organization 83.33%, Stock Card Recording 100%, and Drug Quality Monitoring 100%. These results suggest that drug storage practices at Pharmacy X Lingsar do not fully meet the standards outlined in the Ministry of Health Regulation of the Republic of Indonesia No. 17 of 2024 and the National Agency of Drug and Food Control of the Republic of Indonesia (BPOM RI) of 2018.